Surgical treatment of chest deformities - Azat Satzhanov; Marat Rabandiyarov; Bolat Nagimanov (National Scientific Medical Center, 2017)
The purpose of the study: evaluation of clinical outcomes after thoracoplastic operations, including D. Nass in children with various forms of chest deformities. Methods: 28 thoracoplastic surgeries were performed on the basis of the Zhambyl Regional Children's Hospital from 2015, and 3 of them in cooperation with specialists from the UMC "NSMC". By sexual ratio, boys prevailed (1:3,6). According to the types of deformities 55.6% of the pectus excavatum, 21.4% of the Poland syndrome, 14% of the pectus carinatum. All the children underwent radiological studies: radiography, CT with the defnitions of the Gyzick and Haller indexes. Results: Indication for an operative intervention with a funnel-shaped cosmetic defect of the chest, the Haller index is more than 3.25; the Gizyck index is less than 0.65. The average duration of operations was 56.39 ± 1.40 min, the time spent in the intensive care unit was 1.14 ± 0.12 days, and the time spent in the pediatric orthopedics department was 12.35 ± 1.15 days. Based on the results of IG in the pre-operative period averaged 0.59, after the operation the mean IG increased to 1.00, which shows a correction of the chest. Diﬀerences of IG in the preoperative and postoperative periods demonstrate an increase in the IG index by an average of 85.0% of the initial. Conclusions: According to our observations, the results of D. Nass's operation under endovision, in the postoperative period, show good and satisfactory results to 85% of cases, with a low risk of complications. When fxing the plate, it is recommended to strictly observe the operating technique: epipleural implant insertion, blockage of the ends with short transverse plates, which contributes to the stability of the metal structure.